Pengaruh Keseimbangan Kehidupan Kerja, Stres Kerja dan Perilaku Keselamatan terhadap Kepuasan Kerja pada Pegawai BPBD Provinsi Bengkulu - Farkhan, Muh; JS Pareke, Fahrudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Job satisfaction is an individual's positive mindset that is reflected in employees' opinions about work or the atmosphere at work. Work life balance is achieving a balance between employee's family or personal life and work life. Job stress is an emotional state that arises due to an incompatibility of workload with an individual's ability to deal with the pressures they face. Safety behavior is an action or deed by a person or several employees that minimizes the possibility of an accident occurring to an employee. The purpose of this study is the first to determine the effect of work-life balance on job satisfaction in BPBD Bengkulu Province employees. The second is to determine the effect of work stress on job satisfaction in BPBD Bengkulu Province employees. The third is to determine the effect of safety behavior on job satisfaction in BPBD Bengkulu Province employees. The type of research used is quantitative research, where there is hypothesis testing. The data collection method is by distributing online questionnaires through hand delivery surveys. The population in this study were BPBD Bengkulu Province employees. This study has 26 questions given to respondents. The number of respondents in this study who processed were 120 respondents. The analysis in this study uses SPSS. The results of this study explain that work-life balance has a positive and significant effect on job satisfaction. Job stress has a positive and significant effect on job satisfaction. Safety behavior has a positive and significant effect on job satisfaction. The suggestions given in this study are for further research to conduct similar research with different research objects in order to strengthen previous research. Then you can also add variables and develop a more comprehensive model. This can be the result of more diverse findings in the development of human resource management science.